The Representation of Iraqi Identity in "English for Iraq" for High School Students: A Critical Discourse Analysis - Faisal , Wafaa Mokhlos; Kareem, Thamir Muhammad (Randwick International of Education and Linguistics Science Journal, 2025)
This research tries to examine The Representation of Iraqi Identity in the Iraqi textbook “English for Iraq” concentrating on the reflection of the Iraqi identity in the contents of the book . The study adopts a critical discourse analysis to analyse the identity representation in this textbook . The researcher hypothesizes that “English for Iraq” contains hidden Iraqi identity representation. This paper aims to reveals the hidden Iraqi identity in the textbook “English for Iraq”. The paper adopts a qualitative approach to analyse some samples from the book. The textbook helps with "reconstructing national dignity and rebranding Iraqi identity" in a positive way by telling Hadid's story